2022
DOI: 10.1186/s12871-022-01856-6
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of an adapted opioid-free anesthesia regimen versus conventional general anesthesia in gynecological surgery for low-resource settings: a randomized pilot study

Abstract: Introduction There is scarce data on the safety and efficacy of opioid-free anesthesia (OFA), in resource-limited settings due to the non-availability of dexmedetomidine, the reference OFA agent. We aimed to demonstrate the feasibility, efficacy and safety of a practical OFA protocol not containing dexmedetomidine, adapted for low-resource environments in very painful surgeries like gynecological surgery. Methods We conducted a randomized pilot stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…We planned to observe 50 patients in the OFA group and 50 patients in the OBA group. The number of cases was determined to allow for examining a larger patient collective than had previously been done in smaller randomized studies [2][3][4][5][6]. Normal distribution for continuous data was tested using the Kolmogorov-Smirnov test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We planned to observe 50 patients in the OFA group and 50 patients in the OBA group. The number of cases was determined to allow for examining a larger patient collective than had previously been done in smaller randomized studies [2][3][4][5][6]. Normal distribution for continuous data was tested using the Kolmogorov-Smirnov test.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that 9 (18%) patients in the OBA cohort did not require piritramide. Postoperative opioid consumption (Piritramide) was lower in the OFA group (OFA: 0 [0-3.4], OBA: 6 [3][4][5][6][7][8][9]; P ≤ 0,001). 26 (52%) of 50 patients in the OFA group and 38 (77.6%) of 49 patients in the OBA group received droperidol in the PACU (chi-square test, P = 0.008).…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the post-synaptic inhibitory effect of GABA in the thalamus will be extended. 15 Thiopental also acts on glutamate, adenosine, and nicotinic acetylcholine receptors. 15,16 Anesthesia in this patient was stable, while the patient's hemodynamics were also stable during anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…15 Thiopental also acts on glutamate, adenosine, and nicotinic acetylcholine receptors. 15,16 Anesthesia in this patient was stable, while the patient's hemodynamics were also stable during anesthesia. Furthermore, the patient's CONOX score was stable, with qCON in the range of 40-65 and qNOX in the range of 40-60.…”
Section: Discussionmentioning
confidence: 99%